Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

InsanelyChaotic

  • 3 years ago

Please help me????????????? Solve by using the quadratic formula to solve x2 + 6x = -3.

  • This Question is Closed
  1. anonymous
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    easier to complete the square \[x^2+6x=-3\] \[(x+3)^2=-3+9=6\] \[x+3=\pm\sqrt{6}\] \[x=-3\pm\sqrt{6}\]

  2. DAVIDFF
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    x=-0.5505 , x=-5.449

  3. edpinho
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    write it like this \[x^{2} + 6x +3=0\] a=1 b=6 c=3, now you cam apply the quadretic formula \[\frac{ -b \pm \sqrt{b ^{2}-4ac} }{ 2a }\]

  4. InsanelyChaotic
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    omg thank you guys........!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

  5. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy